Electronic Parts of Small Photovoltaic Power Plant - Benda, Dušan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
The aim of this project is to propose a comprehensive system for the management, control and monitoring of individual components of photovoltaic power plants. This article describes the various methods of approaches to solving each described parts including an outline of the issue. The output of work are functional and tested equipment.
Keywords: switching power supply; photovoltaic power plants; power management; LT8705; LT8490; LTC2946; high efficiency; off-grid